Ruptura amorosa y su incidencia en la salud mental de una paciente de 29 años de la cuidad de Babahoyo - Castro Macias, Mary Liliana (2023)
This case study deals with the love breakup and its impact on the mental health of a 29-year-old girl. The separation, be it courtship or marriage, can affect the state of the mental health of the patient, for this reason, in the development of the case, important data was collected for the progress of the study and its respective elaboration; Psychometric techniques and tools were applied, such as the Beck Depression Inventory with Score 28, which is in the Moderate Depression range; the Hamilton depression test 18 points, stating that it also gives for moderate depression; obtaining in this way through interviews and tests applied a diagnosis that according to the DSM-5 296.22 and CIE 10 code F33.1. Moderate depressive episode. In such a way that a therapeutic scheme was elaborated from the cognitive behavioral approach and it is established so that the patient, with the help of a professional, can carry it out through the sessions.